Scalable Face Image Retrieval using Attribute based Search - Kumar, Pittala Santosh; Sadiq, Mohammad Jaffer (International Journal of Computer Sciences and Engineering, 2014)
Photos are major interests of humans (e.g., family, friends, relatives, etc). Among all those photos, a big percentage of them are photos with human. With the exponentially growing images; Content-based Image Retrieval is an emerging application to retrieve the image from a large set of database. The goal of this research is to retrieve a face image based on attribute-based search. In this work, we aim to detect face image from a given input image and detected facial attributes that contain semantic cues of the face photos to improve content based face retrieval for efficient large-scale face retrieval. In my research, we are using OpenCV to detect the faces.